Thermoplasmatales and Methanogens: Potential Association with the Crenarchaeol Production in Chinese Soils - Li, Fuyan; Zheng, Fengfeng; Wang, Yongli; Liu, Weiguo; Zhang, Chuanlun L. (Frontiers in Microbiology, 2017)
Crenarchaeol is a unique isoprenoid glycerol dibiphytanyl glycerol tetraether (iGDGT) lipid, which is only identified in cultures of ammonia-oxidizing Thaumarchaeota. However, the taxonomic origins of crenarchaeol have been debated recently. The archaeal populations, other than Thaumarchaeota, may have associations with the production of crenarchaeol in ecosystems characterized by non-thaumarchaeotal microorganisms. To this end, we investigated 47 surface soils from upland and wetland soils and rice fields and another three surface sediments from river banks. The goal was to examine the archaeal community compositions in comparison with patterns of iGDGTs in four fractional forms (intact polar-, core-, monoglycosidic- and diglycosidic-lipid fractions) along gradients of environments. The DistLM analysis identified that Group I.1b Thaumarchaeota were mainly responsible for changes in crenarchaeol in the overall soil samples; however, Thermoplasmatales may also contribute to the change in crenarchaeol. This is further supported by the comparison of crenarchaeol between samples characterized by methanogens, Thermoplasmatales or Group I.1b Thaumarchaeota, which suggests that the former two may contribute to the crenarchaeol pool. Last, when samples containing enhanced abundance of Thermoplasmatales and methanogens were considered, crenarchaeol was observed to correlate positively with Thermoplasmatales and archaeol, respectively. Collectively, our data suggest that the crenarchaeol production is mainly derived from Thaumarchaeota and partly associated with uncultured representatives of Thermoplasmatales and archaeol-producing methanogens in soil environments that may be in favor of their growth. Our finding supports the notion that Thaumarchaeota may not be the sole source of crenarchaeol in the natural environment, which may have implication for the evolution of lipid synthesis among different types of archaea.